SARS-CoV-2 in Mozambican primary school-aged children at Maputo City and Province - Bauhofer, Adilson Fernando Loforte (2024)
Funding Information: This work was supported by the \u201Cla Caixa\u201D and the Calouste Gulbenkian foundations in the framework of the Support for Health Research Projects in PALOP Call for Proposals. The findings and conclusions in this article are those of the authors and do not necessarily represent the official positions of the funding agencies. AFLB and AC are fellows of the Deutsche Forschungsgemeinschaft (DFG; grant number JO369/5-1 and JO369/5\u2009\u2212\u20092). LG was supported by Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia, Portugal, (UID/04413/2020, UIDB/00006/2020, and UIDP/00006/2020). The funders had no role in the study design, data collection and analysis, decision to publish, or manuscript preparation. Publisher Copyright: © The Author(s) 2024.